Identification of race: a three-dimensional geometric morphometric and conventional analysis of human fourth cervical vertebrae in adult Malaysian population / Ja Young Shin ... [et al.] - Ja, Young Shin; Alias, Aspalilah; Chung, Eric; Wei, Lin Ng; Yuan, Seng Wu; Quan, Fu Gan; Khin, Myo Thu; Ker, Woon Choy (Faculty of Medicine, Universiti Teknologi MARA, 2021)
Introduction: Estimation of race plays a significant role in establishing personal identity in forensic anthropology. A cervical vertebra is one of the bones that is least researched in forensic applications. Our study aims to investigate the morphologic variations of the fourth cervical vertebrae (C4) between the different major races in the adult Malaysian population using a three-dimensional (3D) geometric morphometrics method. Methods: Computer tomography images of C4 vertebra, which consist of 386 subjects (169 Malay, 82 Chinese, and 135 Indian) were collected retrospectively from University of Malaya. Twenty-eight landmarks were placed on the images. Procrustes MANOVA, canonical variates analysis (CVA), discriminant function analysis (DFA), and linear measurement were performed using Planmeca Romexis, Checkpoint Stratovan, Morpho J, and Graphpad Prism software respectively to analyze the morphological variations of C4. Results: Procrustes MANOVA showed significant differences in the shape (p <0.0001) and centroid size (p = 0.0003) of the C4 vertebra between races. Canonical variate analysis showed significant differences for Mahalanobis (p <0.0001) and Procrustes (p <0.0001) distances among races. Besides that, a cross-validation value of 66.5% was demonstrated by discriminant function analysis. The use of linear measurements reveals no significant differences between the races, these measurements are the vertebral body height, anterior-posterior length of the vertebral body, length of superior articular facet, and spinous process length. Both intra- and inter- observational reliabilities showed that acceptable human errors for measurement accuracy. Conclusions: Morphologic variations in the shape of C4 can assist in race estimation of the adult Malaysian population using the 3D geometric morphometric approach.